2000
DOI: 10.1177/089826430001200203
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Hip Fractures and Socioeconomic Position

Abstract: The results indicate that hip fracture incidence varies as a function of the income level of the ZIP Code area where the population resides. Implications for targeting prevention programs within local areas with low median income are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
40
2
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 29 publications
7
40
2
2
Order By: Relevance
“…Two other more recent studies confirmed the inverse association between individual income and risk of hip fracture [9,27]. Our results are in accordance with works based on area-level socioeconomic indicators in the United States, United Kingdom, and Scandinavia which found an increased risk of hip fracture in areas of lower socioeconomic condition [12][13][14][15]. One possible pathway is the risk of unhealthy lifestyles in deprived areas.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Two other more recent studies confirmed the inverse association between individual income and risk of hip fracture [9,27]. Our results are in accordance with works based on area-level socioeconomic indicators in the United States, United Kingdom, and Scandinavia which found an increased risk of hip fracture in areas of lower socioeconomic condition [12][13][14][15]. One possible pathway is the risk of unhealthy lifestyles in deprived areas.…”
Section: Discussionsupporting
confidence: 92%
“…However, there has been only limited data regarding individual socioeconomic conditions [8][9][10] and in particular area-level socioeconomic conditions as a risk factor of hip fracture, and they tend to produce inconsistent conclusions [11]. While an increased risk of hip fracture was found in areas of lower socioeconomic conditions [12][13][14][15], other studies suggested that area-level socioeconomic conditions were not significantly related to the risk of hip fracture [16,17] particularly in the oldest old population [13]. Two reasons may explain these inconsistent results.…”
mentioning
confidence: 99%
“…Socioeconomic status has been identified as a factor in hip fractures. [13][14][15] Hip fractures are also reported to be more common in urban areas 16,17 and more northern latitudes. 18 Diabetes is a significant risk factor for fractures, 19,20 and any putative benefit of type 2 diabetes in terms of enhanced bone mass appear to be overwhelmed by other adverse consequences of this disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Data relating to the relationship between SES and the risk of osteoporotic fracture has provided varied results [15][16][17][18][19], and to date, there has been no systematic review of this relationship. The aim of this study was to systematically review the literature to examine the relationship between different individual indicators of SES (income, education, type of occupation, type of residence, and marital status) and risk of osteoporotic fracture.…”
Section: Introductionmentioning
confidence: 99%